Development of a novel hand cleansing product for low-income contexts: the case of tab soap - Brial,E; Aunger,R; Muangi,WC; Baxter,W (PLoS One, 2023)
Handwashing with soap is a widely advocated public health measure, but seldom practiced, partly because it is often difficult (especially outside of rich Western country contexts) to make both soap and water readily available in relevant situations. This study used both Behaviour Centred Design and Human Centred Design to guide development of a novel hand cleansing technology appropriate for the context of post-toilet hand cleansing in resource-poor societies. Extensive prototyping and field testing resulted in the pilot production of 'tab' soap, a small but durable single-use, decomposable substrate embedded with soap. It can be produced in dispenser roll or tear-off formats. With this affordable solution, one may use soap without worrying about contamination pretty much anytime and anywhere. A small-scale field test showed that all poor households in rural and peri-urban areas in Tanzania included in the proof-of-concept study (N = 12 households) would use the product reliably over the medium term. Tab soap awaits full-scale production and marketing but could make hand cleansing a more popular practice around the world.